LIVELIHOOD ASSETS OF FISH FARMERS IN TIWINGAN LAMA VILLAGE - Faisal Arif Setiawan; Karunia Puji Hastuti; Akhmad Munaya Rahman; Eva Alviawati (Universitas Lambung Mangkurat, 2021)
During 2019 the Riam Kanan Reservoir had a decrease in water level due to drought. As a result, the income of fish farmers has decreased. This study aims to determine the livelihood assets of fish farmers as long as the pond does not provide maximum income. The research sample is fish farmers as many as 90 respondents. Livelihood Asset Questionnaire refers to DFID. The results showed that the livelihood assets of fish farmers had natural capital of 66, physical capital of 62, human capital of 42, financial capital of 14, and social capital of 11. Attention to financial and social capital needed to be increased to reduce social vulnerability in fish farming families.